The Role and Involvement of Indonesian Ministries and Local Institutions in Handling Rohingya Refugees in Aceh - Kesuma, T. Meldi; Kadir, M. Yakub Aiyub; Siregar, M. Ridha; Halim, Hendra; Siregar, Muhammad Rizqi; Humaira, Radhia; Nisva, Raisa Ullya; Saddaq, Mizan; Maulana, M. Rizki (Journal of Legal and Cultural Analytics, 2024)
This study investigates the involvement and role of Indonesian government ministries and agencies in managing Rohingya refugees in Aceh. It explores key factors influencing the refugee situation, including policy frameworks, resource allocation, and inter-agency coordination. Using qualitative interviews with officials from relevant departments, the research provides an in-depth analysis of the challenges and strategies employed. Findings highlight significant gaps in coordination and resource management, suggesting the need for enhanced policies and greater international cooperation. The study contributes to the understanding of refugee management in Indonesia and offers recommendations for improving policy implementation and support mechanisms for refugees.